Cost-effectiveness of the controlled temperature chain for the hepatitis B virus birth dose vaccine in various global settings: a modelling study. Issue 6 (June 2018) - Scott, Nick; Palmer, Anna; Morgan, Christopher; Lesi, Olufunmilayo; Spearman, C Wendy; Sonderup, Mark; Hellard, Margaret
Summary: Background: The controlled temperature chain (CTC) strategy allows vaccines to be kept outside the cold chain for a short period of time. In remote rural areas, the CTC strategy for the hepatitis B virus (HBV) birth dose vaccination could improve its geographical coverage and timeliness of delivery, but with additional outreach costs. We assessed the cost-effectiveness of the CTC strategy for the HBV birth dose across six world regions and 72 countries according to their HBV prevalence, delivery costs, and birth dose coverage and timing. Methods: By use of a mathematical model of perinatal HBV transmission and disease progression, we calculated per 1000 births the total HBV-related disability-adjusted life-years (DALYs) and costs, including vaccine delivery costs and costs associated with HBV-related disease, with and without the CTC strategy. Findings: A CTC strategy produced health benefits in all regions and was cost-saving in the regions of east Asia and Pacific, Latin America and Caribbean, sub-Saharan Africa, and north Africa and Middle East. The CTC strategy cost US0·15 (IQR −7·11 to 4·75) per DALY averted in the central and eastern Europe and central Asia region and 79·72 (66·47 to 94·47) in the south Asia region. Within individual countries, more savings were achieved and more DALYs averted in areas with above average HBV prevalence, below average birth dose coverage, or later than average birth dose delivery. Interpretation: A CTC outreach strategy that improves the timing and coverage of the HBV birth dose vaccination is likely to be cost-saving and reduce the burden of HBV infection associated with perinatal transmission. Funding: Burnet Institute.